Reciprocal series involving Horadam numbers - Adegoke, K.; Frontczak, R.; Goy, T. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 511.176 We evaluate some new three-parameter families of finite reciprocal sums involving Horadam numbers. We are also able to state the results for the associated infinite sums. Some Fibonacci and Lucas sums are presented as examples.